Walnuts (Juglans regia) Chemical Composition and Research in Human Health. Issue 8 (10th June 2016) - Hayes, David; Angove, Michael J.; Tucci, Joe; Dennis, Christina
Abstract : Walnuts are among the most widely consumed commercially grown tree nuts in the world. Many health benefits have been claimed for the consumption of these, including reduced risk of cardiovascular disease, coronary heart disease, type II diabetes treatment, and prevention and treatment of certain cancers, and the lessening of symptoms attributed to age-related and other neurological disorders. The health-promoting benefits of walnut consumption are ascribed to its fatty acid profile, which is rich in polyunsaturated fatty acids with a particularly high ω3:ω6 ratio—the highest among all the tree nuts. The content of polyphenols and other phytochemicals in walnuts, with their claimed cytotoxic properties, also make them an attractive candidate for research for the prevention of free radical-induced nucleic acid damage. Research of walnut consumption in humans and animals employing a range of data sets and statistical methods suggest that walnuts may be considered a safe potential nutraceutical or possibly pharmaceutical substance. Nevertheless, few reviews of scientific research on the proposed benefits of these nuts exist, in spite of the numerous claims attributed to them in the lay media. This brief review article attempts to disseminate much of the information surrounding walnut consumption, and human health benefits, to other scientists and the interested general reader.